GAMIFICATION OF EDUCATION: ANALYSIS OF EXPERIENCE AND CRITIQUE - KOROTKOVA, VLADISLAVA S.; KOROTKOV, EVGENIY A. (Челябинский гуманитарий, 2025)
This article explores the challenges of integrating gamification into educational disciplines and ways to overcome them. It analyses recently published systematic reviews on the gamification of education, concluding that gamification in education significantly increases student motivation and engagement, particularly in e-learning, and helps overcome anxiety in foreign language learning. However, many studies have been criticized due to shortcomings in applied research and a weak connection to theoretical foundations. To implement gamification successfully, teachers must have a thorough understanding of its theories and the necessary resources. The article emphasizes the importance of understanding gamification theory for teachers to assess the advantages and disadvantages of its use in the classroom. The article summarizes the experience of using gamification in English language classes at a university. The article also addresses the challenges faced by teachers in gamifying education, including the deteriorating quality of digital platform services, students’ reluctance to cope with the boredom of routine work, and the increasing workload of teachers. Based on an analysis of research and personal experience with gamification in education, the paper concludes that, despite positive results, there is a risk that this tool will not meet expectations. It emphasizes the importance of considering the interests of both students and teachers when implementing gamification, and proposes the creation of a work group to optimize this process. Further research in the field of e-learning is also addressed.